Video Conference Application with File Attachment - Dini Yocta Prabayanti; Ade Eviyanti (Universitas Muhammadiyah Sidoarjo, 2021)
Communication today is a human need as a social creature. In accordance with technological advances, communication can be in the form of instant messages such as WhatsApp, telegram and video converence, video converence services can communicate face- to-face with other users. Video converence in the most popular appstore and playstore, namely zoom meetings. Zoom meting makes it easy for users to create and schedule online meetings. the application is not equipped with file sharing services. In this case, users find it difficult to send files to other users who join the online meeting. The video converence application with a file attachment makes it easy in the morning for online meeting users to create, schedule and share files into online meetings. It is hoped that with this application users can easily share files in online meetings. This system is made with a simple interface design that is easy to understand for using the application. The purpose of this research is to make it easier for people to conduct online meetings. The method used is the waterfal method, while the data collection technique is quantitative data technique. The desired result of the research is to make it easier for people to conduct online meetings and send data through this application without having to open another application.